(3MGTjI Ydi TQM GdgOGjIs - (3GdMSjfj, aNQ GdOjf, eMeO Hf GdMSjf, J (B968 (3g`s ((3HGbQ Hf SdWGf eMehOs)
(3ChdgG (B:s
(3GdMeO ddg (B..(3Ef TQM GdgOGjI GdCKjQjI ddaGVd GdChMOj GdbGVj ceGd GdOjf MSjf GdeHjOj bO HdZ aj GdGTJgGQ cGdTeS aj QGHYI GdfgGQ hEfj cfJ SGdaG fGXQG aj Objbg hLdjdg eZfjG Yf ELeGdg hJaUjdg (B...s
(3BNQgG (B:s
... (3Cbhd bO YQaJ Cf GdHQgGf dh Je CaGO Cf GdbhI GdLSeGfjI dG Jbhi Ydi GdJMQjc GdZjQ GdeJfGgjI hdG hGSWI hdYd hLg GdJCed Cf GdfaS hGMOI cja jUOQ Yfg GdBKGQ ZjQ GdeJfGgjI (B... (3hGdMeO ddgs
(3JHUQI GdYfhGf (B:s
(3TQM Ydi TQM GdejHOjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\ 249s
(3GdPQjYI (B14\2055s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs